Design and development of a building façade integrated asymmetric compound parabolic photovoltaic concentrator (BFI-ACP-PV) - Lu, Wei; Wu, Yupeng; Eames, Philip (Elsevier, 2018)
Building Integrated PV and Concentrating PV can generate electricity onsite and provide savings in materials and electricity costs, as well as protecting buildings from weather. In this paper, a novel truncated stationary asymmetric compound parabolic photovoltaic concentrator with a geometric concentration ratio of 2.0 has been designed and experimental characterised. The designed system is suitable for building façade application, especially for vertical façade. It has wide acceptance half angles of 0° and 55°, this acceptance angle range enables the concentrator to operate year-round at its geometric gain in most of the UK and EU climatic condition. A comprehensive indoor test was carried out to evaluate the electrical and thermal characterisation of the developed Building Façade Integrated Asymmetric Compound Parabolic Photovoltaic concentrator (BFI-ACP-PV) system, and also the factors that affect the power output of the developed system. The experimental results showed that the developed BFI-ACP-PV system has the potential to increase the power output per unit solar cell area by a factor of 2, when compared with a non-concentrating PV system. Subsequently, a Phase Change Material (PCM) system was integrated to the rear of the BFI-ACP-PV system to moderate the PV temperature rise and maintain good solar to electrical conversion efficiency. It was found out that the electrical conversion efficiency for the BFI-ACP-PV coupled PCM system was increased by over 5% compared with a similar system with no PCM integrated at the rear, when the incident solar radiation intensity was 280 W/m2, this value increased by over 10% for an incident solar radiation intensity of 670 W/m2.